Learning from Indonesia: A systematic literature review on the implementation of traditional Indonesian games for mathematics education - Qirom, Muhamad Syahidul; Dadang Juandi (Beta: Jurnal Tadris Matematika, 2023)
[English]: As part of the culture, traditional games have a positive impact on the teaching and learning process of mathematics. Looking at the facts in the field related to problems in learning mathematics, such as students' lack of motivation to learn mathematics and difficulties in understanding mathematics, teachers can use traditional games as a solution to these problems. Therefore, this study aims to investigate the impact of Indonesian traditional games on learning mathematics. Systematic literature review (SLR) was used as the method in this study and PRISMA 2020 as the research framework. In this study, there were five inclusion criteria: the documents were from published articles, the traditional games had to be from Indonesia, the documents were in English, they were specific to the subject of mathematics, and the research objective of the articles was to identify the impact of the application of traditional games on mathematics learning. There were 22 articles eligible for review to answer the research questions. The results showed, 1) Indonesian traditional games were shown to have potential effects to support cognitive, psychomotor, affective, mathematical process skills, and 21st century skills; 2) the Java region was the most frequent location for research on the implementation of traditional games; 3) Numbers and Geometry are more frequently taught using traditional games compared to other mathematics topics; 4) primary school students are the most frequent sample in the implementation of traditional games; and 5) design research is the most frequently used research type in the implementation of traditional games in mathematics learning. This research provides information on traditional games that can be implemented in mathematics learning and provides evidence that traditional games do have a positive effect on learning mathematics. [Bahasa]: Sebagai bagian dari budaya, permainan tradisional memiliki dampak positif terhadap proses belajar mengajar matematika. Melihat fakta di lapangan terkait permasalahan dalam pembelajaran matematika, seperti kurangnya motivasi siswa belajar matematika hingga kesulitan dalam memahami matematika, maka guru dapat menggunakan permainan tradisional sebagai solusi terhadap masalah tersebut. Oleh karena itu, penelitian ini bertujuan untuk menyelidiki dampak permainan tradisional Indonesia terhadap pembelajaran matematika. Tinjauan literatur sistematis (SLR) digunakan sebagai metode dalam penelitian ini dan PRISMA 2020 sebagai kerangka kerja penelitian. Pada penelitian ini, terdapat lima kriteria inklusi yakni dokumen berasal dari artikel yang telah dipublikasikan, permainan tradisional harus berasal dari Indonesia, dokumen menggunakan bahasa Inggris, dikhususkan untuk mata pelajaran matematika, dan tujuan penelitian dari artikel tersebut adalah mengidentifikasi dampak penerapan permainan tradisional terhadap pembelajaran matematika. Terdapat 22 artikel yang memenuhi syarat untuk ditinjau untuk menjawab pertanyaan penelitian. Hasil penelitian menunjukkan, 1) permainan tradisional Indonesia terbukti memiliki efek potensial untuk mendukung kemampuan kognitif, psikomotorik, afektif, keterampilan proses matematika, dan keterampilan abad ke-21; 2) wilayah Jawa merupakan lokasi yang paling sering menjadi tempat penelitian implementasi permainan tradisional; 3) Bilangan dan Geometri lebih sering diajarkan dengan menggunakan permainan tradisional dibandingkan dengan topik matematika yang lain; 4) siswa sekolah dasar merupakan sampel yang paling sering dijadikan subjek dalam implementasi permainan tradisional; dan 5) design research merupakan jenis penelitian yang paling sering digunakan dalam penelitian implementasi permainan tradisional dalam pembelajaran matematika. Penelitian ini berkontribusi dalam menyajikan informasi terkait permainan tradisional yang dapat diimplementasikan dalam pembelajaran matematika dan menjadi bukti bahwa permainan tradisional memang memiliki efek positif terhadap pembelajaran matematika.